The Discernment of Spirits Assessing Visions and Visionaries in the Late Middle Ages - Anderson, Wendy Love (Mohr Siebeck, 2011)
Die Unterscheidung der Geister. Die Einschätzung der Visionen und der Visionäre im Spätmittelalter.
PublicationDate: 20200831
Keywords: Body Turn -- Discernment of Spirits -- Medieval Mysticism -- Medieval History of Christianity -- Kirchengeschichte -- Antike Religionsgeschichte -- Array